감마분광분석을 이용한 226Ra의 직접 측정방법에 대한 적용성 평가 - 지영용(Young-Yong Ji), 정근호(Kun Ho Chung), 임종명(Jongmyoung Lim), 김창종(Chang-Jong Kim), 장미(MEE JANG), 강문자(Mun Ja Kang), 박상태(Sang Tae Park), 우주희(Zu-Hee Woo ), 구본철, 서보균 (Journal of nuclear fuel cycle and waste technology (Online), 2014)
HPGe 감마선 검출기를 이용하여 226Ra의 방사능을 직접 측정방법의 경우, 226Ra의 186.21 keV 감마선이 235U에서 방출되는 185.7 keV 감마선에 의한 간섭을 받기 때문에 피크면적의 계산에서 반드시 보정이 필요하다. 비록 분해능이 아주 우수한 HPGe 검출기를 사용한다 하더라도 그리고 분광시스템의 채널수를 최대로 늘린다고 할지라도 약 0.5 keV 차이의 두 감마선 피크를 분리해 내기란 현실적으로 어려운 일이다. 본 연구에서는 감마분광분석을 이용한 226Ra의 직접 측정방법에 대한 적용 성을 평가하기 위하여, 여러 가지 간섭피크 보정들을 이용한 직접 측정방법을 조사하였다. 이를 원료물질 및 공정부산물 시 료들에 적용함으로써 직접 측정방법들에서 그 측정 불확도, 직선성 및 적용범위 등을 평가하였다. 최종적으로 방사평형 관 계를 이용하여 226Ra의 방사능을 측정하는 간접 측정방법으로부터 얻은 214Pb 및 214Bi의 결과를 직접 측정방법의 결과와 비 교함으로써 최적의 측정방법을 유도하였다. In the case of the direct measurement of 226Ra using a HPGe gamma-ray spectrometer, the interference between gammarays with 186.21 keV of 226Ra and 185.7 keV of 235U should be corrected to calculate the net peak area in the energy spectrum. In general, it is very difficult to conduct peaks stripping with difference of about 0.5 keV, although a HPGe with the superior resolution is applied and the maximum channels is applied to the spectrometer. In this study, several interference correction techniques in the direct measurement were surveyed to evaluate the feasibility for the measurement of 226Ra using the gamma-ray spectrometery. Applying the interference corrections to the analysis of raw materials and by-products, the method validation for the direct measurement of 226Ra was conducted by evaluating the measurement uncertainty, linearity, and range. As a result, the optimum method of the interference correction was selected by comparing with the indirect measurement of which progenies of 226Ra, such as 214Pb and 214Bi, were analyzed in the secular equilibrium state.